Potential theory for quasiliniear elliptic equations - Azeddine Baalal; A. Boukricha (Electronic Journal of Differential Equations, 2001)
We discuss the potential theory associated with the quasilinear elliptic equation $$ -{ m div}(A(x,abla u))+B(x,u)=0. $$ We study the validity of Bauer convergence property, the Brelot convergence property. We discuss the validity of the Keller-Osserman property and the existence of Evans functions.